Review Article: Analysis of Drug-Related Problems (DRPs) in Diarrheal Disease Therapy - Putranto, Diouf Maulana Dwi; Pebrianti, Dea Riski; Zaneta, Nabila Destia; Ulya, Tuhfatul; Hasina, Raisya; Sari, Tri Purma (Jurnal Biologi Tropis, 2025)
Diarrhea is one of the most common diseases in children and has the potential to cause various complications if not treated properly. Inappropriate treatment can trigger Drug Related Problems (DRPs) that affect the effectiveness of therapy. To identify and analyze the types of Drug Related Problems (DRPs) and recommended interventions in the treatment of diarrhea to support safe, effective, and rational drug use. A literature review was conducted by searching the PubMed and Google Scholar databases. A total of 10 articles that met the inclusion criteria were analyzed. The most common types of DRPs found were indications without therapy (7-45%), inappropriate dosing (both underdose 8-27% and overdose 7-35%), therapy without indication (10-85%), and drug interactions (12-56%). The main problems lie in the inaccuracy of clinical evaluation and irrational drug administration. DRPs in the treatment of childhood diarrhea are still common and have an impact on patient outcomes. Optimizing the role of pharmacists through medication reviews, dose adjustments, monitoring potential drug interactions, and educating health workers are key strategies for minimizing DRPs and improving treatment success.